GET4 is a novel driver gene in colorectal cancer that regulates the localization of BAG6, a nucleocytoplasmic shuttling protein. Issue 1 (10th November 2021) - Koike, Kensuke; Masuda, Takaaki; Sato, Kuniaki; Fujii, Atsushi; Wakiyama, Hiroaki; Tobo, Taro; Takahashi, Junichi; Motomura, Yushi; Nakano, Takafumi; Saito, Hideyuki; Matsumoto, Yoshihiro; Otsu, Hajime; et al.
Abstract: Colorectal cancer (CRC) is one of the most common types of cancer and a significant cause of cancer mortality worldwide. Further improvements of CRC therapeutic approaches are needed. BCL2‐associated athanogene 6 (BAG6), a multifunctional scaffold protein, plays an important role in tumor progression. However, regulation of BAG6 in malignancies remains unclear. This study showed that guided entry of tail‐anchored proteins factor 4 (GET4), a component of the BAG6 complex, regulates the intercellular localization of BAG6 in CRC. Furthermore, GET4 was identified as a candidate driver gene on the short arm of chromosome 7, which is often amplified in CRC, by our bioinformatics approach using the CRC dataset from The Cancer Genome Atlas. Clinicopathologic and prognostic analyses using CRC datasets showed that GET4 was overexpressed in tumor cells due to an increased DNA copy number. High GET4 expression was an independent poor prognostic factor in CRC, whereas BAG6 was mainly overexpressed in the cytoplasm of tumor cells without gene alteration. The biological significance of GET4 was examined using GET4 KO CRC cells generated with CRISPR‐Cas9 technology or transfected CRC cells. In vitro and in vivo analyses showed that GET4 promoted tumor growth. It appears to facilitate cell cycle progression by cytoplasmic enrichment of BAG6‐mediated p53 acetylation followed by reduced p21 expression. In conclusion, we showed that GET4 is a novel driver gene and a prognostic biomarker that promotes CRC progression by inducing the cytoplasmic transport of BAG6. GET4 could be a promising therapeutic molecular target in CRC. Abstract : GET4 stained more intensely in the nuclei and cytoplasm of colorectal cancer tumor cells than those of normal colon.